The Impact of Organisational Culture on Employee Engagement and Performance - Anena Sheila (Uganda Christian University, 2024)
This study examined the impact of organizational culture on employee engagement and performance at Uganda Christian University (UCU). Through a descriptive cross-sectional design, the research assesses the relationship between organizational culture and employee engagement, analyzes the effects of alignment between organizational values and employee engagement, and identifies additional factors influencing engagement. Utilizing a sample of 40 out of 70 employees across various departments, the study integrates both qualitative and quantitative methods, including open- and closed-ended questionnaires, to provide a comprehensive analysis of the subject. The findings reveal that UCU's organizational culture positively influences employee engagement, particularly in areas such as values, leadership, and work-life balance. However, the study identifies areas for improvement, including collaboration, recognition, and diversity. Core values such as honesty and openness greatly influence employee involvement, while other aspects like having the necessary resources, receiving recognition, and having freedom to make decisions are key to boosting motivation and job happiness. These findings match with theories by Herzberg and Deci and Ryan, which highlight the importance of recognition and freedom in increasing engagement. The study suggests improving recognition and reward systems, creating a cooperative and welcoming atmosphere, and making sure the company's values match what employees expect. Following these suggestions can help fix existing issues, boost employee engagement, and support UCU's goal of having a supportive and inclusive workplace. Overall, the study shows how important a company's culture and values are for employee engagement and provides useful ideas for making the workplace better at UCU.